Genome-wide association study of clinical parameters in immunoglobulin light chain amyloidosis in three patient cohorts - Meziane, Iman; Huhn, Stefanie; Weinhold, Niels; Nickel, Jolanta; Jauch, Anna; Goldschmidt, Hartmut; Hegenbart, Ute; Schönland, Stefan (Haematologica, 2017)
Immunoglobulin light chain (AL) amyloidosis is a progressive plasma cell dyscrasia which is characterized by the deposition of amyloid fibers derived from immunoglobulin light chain or their fragments systemically in many organs.[1][1] The characteristics of amyloids relate to disease severity and
Gesehen am 30.10.2018